2019
DOI: 10.1186/s40249-019-0603-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of active case finding in reducing patient incurred catastrophic costs for tuberculosis in Nepal

Abstract: BackgroundThe World Health Organization (WHO) End TB Strategy has established a milestone to reduce the number of tuberculosis (TB)- affected households facing catastrophic costs to zero by 2020. The role of active case finding (ACF) in reducing patient costs has not been determined globally. This study therefore aimed to compare costs incurred by TB patients diagnosed through ACF and passive case finding (PCF), and to determine the prevalence and intensity of patient-incurred catastrophic costs in Nepal.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 26 publications
4
78
1
1
Order By: Relevance
“…However, they would have been diagnosed later, and potentially at greater cost to them and in a poorer state of disease. [22,23] Study limitations include that both intervention and control districts were not randomly selected and may not be representative of all Mozambican health facilities. The existence of differences between intervention and control districts that could explain the results besides the exposure to the intervention cannot be completely excluded.…”
Section: Plos Onementioning
confidence: 99%
“…However, they would have been diagnosed later, and potentially at greater cost to them and in a poorer state of disease. [22,23] Study limitations include that both intervention and control districts were not randomly selected and may not be representative of all Mozambican health facilities. The existence of differences between intervention and control districts that could explain the results besides the exposure to the intervention cannot be completely excluded.…”
Section: Plos Onementioning
confidence: 99%
“…The results showed that the economic burden on TB-affected households was high, especially due to costs relating to travel, lost income, and associated with seeking a mixture of both public and private healthcare. The prevalence of catastrophic costs of TB-affected households (total TB associated costs of more than 20% of the same TB-affected household's annual income) [13,43,44] was high in both studies (53% and 49%, respectively) [42].…”
Section: Ongoing Studies Addressing the Socioeconomic Impact Of Tb Inmentioning
confidence: 74%
“…In order to improve the diagnosis [32][33][34][35], treatment [36,37] and TB prevention services [38][39][40], a lot of research have been carried out around the world. A study from Nepal found that active case nding could reduce catastrophic costs [41]. And the WHO milestones can only be achieved within the context of progress towards universal health coverage (UHC) [1].…”
Section: Discussionmentioning
confidence: 99%